New findings of halimedacean algae from the Late Triassic Dachstein Limestone of the Northern Calcareous Alps : (Hochschwab Area, Styria, Austria) - Schlagintweit, Felix (Array, 2008)
Summary: Two taxa of halimedacean algae are recorded from the Upper Triassic lagoonal Dachstein Limestone (Norian-Rhaetian) of the Hochschwab area in the south-eastern part of the Northern Calcareous Alps of Austria. They are described in open nomenclature as Halimeda? sp. 1 and Halimeda? sp. 2. In contrast to the widespread occurrence of dasycladalean algae, representatives of Halimedaceans are very rare. These findings are the second record in the Northern Calcareous Alps since FLÜGEL (1975)